PRAKTIK PERDAGANGAN ILEGAL PAKAIAN BEKAS DI LINTAS BATAS DAN DAMPAKNYA TERHADAP MASYARAKAT LOKAL (STUDI KASUS PERBATASAN KABUPATEN BENGKALIS) - Bistianita, Yana; Retnaningsih, Umi O. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Illegal trade is an important issue in Indonesia. One form of illegal trade is the existence of the used clothing trade. Bengkalis Regency, which is an area that interacts directly with Malaysia and is a cross-border location of the Malacca Strait, has the potential for various violations such as clothing smuggling, which is considered to be disturbing the national industry.The theory used in this research is the Mercantilism approach using protectionism theory, where the state tries to protect the domestic economy through various policies issued in accordance with the results of the 2015 Analysis Report on the Import of Used Clothes by the Indonesian Ministry of Trade. The research method used in this study is a qualitative research method with research data collection techniques, namely primary and secondary data. Through interview and observation techniques with semi-structured interview guidelines with the participants conducted for 2 months.The results of research found that trade in used clothes across national borders does not always have a negative impact on a country, but can actually have many positive impacts, especially for local communities in border areas. Positive economic impacts for sellers and owners of the sewing industry, positive social impacts for buyers, as well as positive and negative impacts on environmental aspects.Â Â Keywords: Used Clothes, Smuggling, Cross-border, Government Policy.